Separation of Butanol from Abe Mixtures by Sweep Gas Pervaporation Using a Supported Gelled Ionic Liquid Membrane: Analysis of Transport Phenomena and Selectivity - Romero-Figueroa, J; Merlet-Venturelli, G; Plaza, A (2013)
The separation of acetone-butanol-ethanol mixtures (ABE) from aqueous solutions, which are produced in ABE fermentation processes, is carried out by sweep gas pervaporation using gelled supported ionic liquid membranes and by membrane evaporation. The membranes were synthesized by the gelation of an ionic liquid ([bmim][PF6]) into the porosity of polytetrafluoroethylene (PTFE) hollow fibers. The performance of the membranes used in sweep gas pervaporation is compared with the membrane evaporation process using the same hollow fiber support without IL in order to verify the selectivity contributed by the gelled ionic liquid gap formed in the membrane pores. Improved butanol/ethanol selectivity was verified for gelled IL membranes in pervaporation experiments compared to the evaporation process. A resistance-in-series model was developed to simulate the pervaporation process. The model predictions were in good agreement with the experimental results. IL membranes are found to have potential for separation of butanol from the ABE mixtures by pervaporation. © 2013 Elsevier B.V.